2022
DOI: 10.21203/rs.3.rs-2012008/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Branched-Chain Amino Acids on Patients Undergoing Hepatic Intervention: A Meta-Analysis of Randomized Controlled Trials

Abstract: BACKGROUND: The benefits of branched-chain amino acid (BCAA) administration after hepatic intervention in patients with liver diseases remains unclear. We conducted a systematic review and meta-analysis to evaluate the effects of BCAA on patients undergoing hepatectomy, trans-arterial embolization, radiofrequency ablation. METHODS: Relevant randomized controlled trials (RCTs) were obtained from PubMed, EMBASE, and Cochrane Library databases. A meta-analysis was performed to calculate the pooled effect size by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…As for the liver enzymes, the findings of this study revealed that the administration of PN with amino acid-intralipid decreased the ALT, AST, and Bil, which was in line with the report of Liu et al The combination itself could further reduce ALT and AST (29). In addition, Navaratnarajah et al found that the children using SMOFlipid-intralipid had lower BL levels at the end of the study (30); however, Hsu et al established that amino acid administration had no effect on liver tests (31). The reason for the difference in results could be attributed to the types of diseases affecting the patients, as some studies were conducted on cases with liver diseases, preterm infants, or in animal laboratory environments.…”
Section: Estimated Marginal Means Of Diuresis Patientsupporting
confidence: 90%
“…As for the liver enzymes, the findings of this study revealed that the administration of PN with amino acid-intralipid decreased the ALT, AST, and Bil, which was in line with the report of Liu et al The combination itself could further reduce ALT and AST (29). In addition, Navaratnarajah et al found that the children using SMOFlipid-intralipid had lower BL levels at the end of the study (30); however, Hsu et al established that amino acid administration had no effect on liver tests (31). The reason for the difference in results could be attributed to the types of diseases affecting the patients, as some studies were conducted on cases with liver diseases, preterm infants, or in animal laboratory environments.…”
Section: Estimated Marginal Means Of Diuresis Patientsupporting
confidence: 90%